Adipose-Derived Stem Cells Are an Efficient Treatment for Fistula-in-ano of Japanese Rabbit. (22nd October 2019) - Qin, Xiao; Wang, Peng; Huang, Yongming; Li, Yansen; Chao, Min; Wang, Wei
Abstract : Fistula-in-ano (FIA, anal fistula) treatment remains a surgical challenge for coloproctologists. Adipose tissue-derived stem cells (ADSCs) are a new frontier in the treatment of FIA. In this study, we established a FIA model of Japanese rabbit and evaluated the effect of four treatments on fistula healing: ADSC transplantation, acellular small intestinal submucosa (ASIS), noncutting seton, and PBS as negative control. High-throughput RNA sequencing was also performed to investigate the anal tissue (normal and ADSC treatment group) expression profile of mRNA. Our data showed that ADSC treatment had the shortest time to promote fistula healing compared to the other treatments, and fistula filled with new adipose tissue and muscle cells without scar. Gene Ontology (GO) analysis of RNA-seq data showed that the differential genes are enriched in system development and animal organ development. Taken together, our findings demonstrate that ADSCs rapidly promote fistula healing through differentiation, a promising stem cell therapy for FIA. The rabbit is an effective animal model for evaluating FIA therapeutic options.